Can Clinical Outcomes Be Improved, and Inpatient Length of Stay Reduced for Adults With Diabetes? A Systematic Review - Friel, Kathleen Michelle; McCauley, Claire; O’Kane, Maurice; McCann, Michael; Delaney, Geraldine; Coates, Vivien (Frontiers in Clinical Diabetes and Healthcare, 2022)
Aim To examine the efficacy of clinical practice strategies in improving treatment and clinical outcomes and reducing length of hospital stay for inpatients with Type 1 and Type 2 diabetes. Background Those living with diabetes experience disproportionately long stays in hospital in comparison to the rest of the population. Clinical staff are largely responsible for the inpatient diabetes care provided, especially relating to blood glucose management. However, keeping blood glucose levels within target ranges can be challenging. With a rising prevalence of diabetes globally and excessive expenditure on this condition, opportunities to reduce length of stay must be prioritised in secondary care. Study Design A systematic review and narrative synthesis. Methods A systematic search of CINAHL, Medline Ovid, Web of Science and SCOPUS databases for research papers relating to adult inpatients with diabetes was conducted for the period 2010–2021. Selected papers were assessed by at least two independent reviewers for inclusion criteria, methodological validity, and data extraction. Eighteen empirical studies were included. Results Eighteen studies spanned a range of inpatient areas relevant to adults with diabetes and examined clinical management innovations, clinical education programmes, multidisciplinary collaborative care and technology facilitated monitoring. The studies explored post intervention clinical outcomes and demonstrated improved glycaemic control with reduced occurrence of hypoglycaemia and hyperglycaemia, decreased healthcare costs and reduced readmissions and length of hospital stay. Conclusions As length of stay is a key performance indicator, made even more relevant since the Coronavirus (Covid-19) pandemic, these results indicate attainable clinical practice strategies to improve treatment and clinical outcomes and reduce length of hospital stay. The result of this review provides a starting point for healthcare professionals and educators to facilitate the translation of such evidence into practice for improving patient outcomes and efficiency of hospital care.